Qualification of Smuggling of Narcotic Drugs, Psychotropic Substances, their Analogues and Precursors or Counterfeit Medicines Committed in Complicity and in Conjunction with Other Crimes - OMELCHUK, Oleh; KRUSHYNSKYI , Serhii (University Scientific Notes, 2020)
The forms of complicity in which the smuggling of narcotic drugs, psychotropic substances, their analogues and precursors or counterfeit medicines may be analyzed and described, namely: by a preliminary conspiracy by a group of persons, as part of an organized crime group and a criminal organization. Their main features are established, by which it is possible to distinguish between and distinguish between a particular form of complicity for further correct qualification of unlawful acts. At the same time, there are some examples of drug smuggling in complicity. Also, the examples of criminal offences stipulated by the current Criminal Code of Ukraine, which are most often committed with the smuggling of narcotic drugs, namely: committing drug smuggling with the participation of officials, obtaining illegal benefits, falsification of medicines with further illegal transportation abroad, financing of terrorist activities, as well as illegal handling of weapons in the commission of the above-mentioned crime, hooliganism. The public danger of such actions is substantiated and established, which causes the need to consider further ways to improve the current legislation in the fight against drug smuggling, which over time becomes a significant scale and negative trends. At the same time, foreign legislation providing for the use of weapons in the commission of drug smuggling is analyzed. The above material was described and a reasonable conclusion was made that the current norm, which provides for the responsibility for the smuggling of narcotic drugs, requires necessary improvements and changes to effectively combat the phenomenon of transnational crime and the correct qualification of the actions of guilty persons.